Soil carbon monitoring using laser-induced breakdown spectroscopy - Ahokas, Joni (2024)
Monitoring soil carbon can be helpful in understanding how different land-use practices sequestrate carbon from the atmosphere. This is important for climate change mitigation as well as the soil well-being. Soil carbon assessment is currently mostly done using dry combustion methods, which require a lot of sample preparation and a laboratory environment. Therefore these methods are not well suited for monitoring purposes, and novel and fast methods for measuring soil carbon concentrations are needed. Laser-induced breakdown spectroscopy is able to remove many of the bottlenecks related to other measurement methods. In this work, optimal measurement parameters are determined and calibration of a laser-induced breakdown spectroscopy setup is performed using a set of samples reference measured with dry combustion. Optimal measurement parameters, including laser wavelength, laser energy, spectrometer delay and exposure time were found and two calibration models for two different sets of samples were created based on these parameters.